2015
DOI: 10.1111/eje.12162
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices surrounding occupational blood‐borne pathogen exposure amongst students in two Chinese dental schools

Abstract: More effective education on prevention and management is required for dental students to reduce the harm caused by occupational exposure. It is important to ensure dental students' knowledge and understanding before allowing them to enter clinical training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
3
25
0
1
Order By: Relevance
“…Unfortunately, previous studies reported that HCW in Saudi Arabia showed low compliance with hepatitis B vaccination, and it became mandatory to structure educational programs to raise the awareness and enhance health-care workers’ compliance with HBV vaccination [26], [37], [38]. It is noteworthy that HBV vaccination compliance was also below expectations among HCW in Brazil, Serbia, Libya, Ethiopia, China and India [10], [11], [25], [26], [27], [28], [35], [36], [42]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, previous studies reported that HCW in Saudi Arabia showed low compliance with hepatitis B vaccination, and it became mandatory to structure educational programs to raise the awareness and enhance health-care workers’ compliance with HBV vaccination [26], [37], [38]. It is noteworthy that HBV vaccination compliance was also below expectations among HCW in Brazil, Serbia, Libya, Ethiopia, China and India [10], [11], [25], [26], [27], [28], [35], [36], [42]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the low compliance with eye protection was reported among DHCW and students in Lebanon, Morocco, India, and China [30], [35], [36], [40], [42]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many authors state that the reporting of both injuries and occupational diseases is not complete [19,27,28]. What is more, so if your profession brings satisfaction (with us 82% of respondents) and it is economically viable.…”
Section: Discussionmentioning
confidence: 99%
“…Maceió, AL, 2014. 26 também demonstrou insatisfação dos alunos participantes, pois a maioria (80%) afirmou que tinham conhecimento incompleto sobre infecções por exposição ocupacional. Quando comparados os períodos da IES(A), foi observado no 5º período maior prevalência de alunos que não sabiam a resposta quando perguntado sobre os patógenos que devem ser pesquisados após um AEMB.…”
Section: Ambas As Ies (Tabela-4) O Tipo De Exposição Com Maior Prevunclassified